Simulation for complete coverage path planning - Win Myat Soe. (2008)
This thesis consits of 2 parts. -Part A-. Coverage path planning is the determination of a path that a robot must take in order to pass over each point in an environment. Applications include vacuuming, floor scrubbing, and inspection. This dissertation presents a simulation study of complete coverage path planning using simple back and fork motion. It also reviews some coverage path planning algorithms and problems.